Processing and characterizations of Bi2O3/BaTiO3 ceramic - Vittayakorn, Wanwilai C.; Banjong, Dondanai; Vittayakorn, Naratip (My University, 2013)
The objective of this work is to provide the process for making BaTiO3-based ceramics by adding bismuth oxide (Bi2O3) into the system. The attention is also focused on synthesis conditions, where sintering temperature exhibits a pronounced effect on phase formation, density, microstructure and dielectric properties of BaTiO3 ceramics doped with different contents of Bi2O3 nanoparticles. The phases of BaTiO3-based ceramics have been prepared by solid state reaction using different Bi2O3 amount and characterized by X-ray diffractometry, Archimedes's method, scanning electron microscopy and dielectric spectroscopy. The results show that single phase of BaTiO3 with no evidence of secondary phase forms in all samples. Abnormal grain growth was found in pure BaTiO3 ceramic with 37.30 μm of average grain size. After added Bi2O3 nanoparticles into system, the grain size significantly decreases and the sintering temperature of BaTiO3-based ceramics efficiently reduces without degrading the dielectric characteristics. © (2013) Trans Tech Publications, Switzerland.
Keywords: Barium titanate; Bismuth oxide; Dielectric property; Sintering temperature